A Fast Alternative to Soft Lithography for the Fabrication of Organ‐on‐a‐Chip Elastomeric‐Based Devices and Microactuators. Issue 8 (8th February 2021) - Ferreira, Daniel A.; Rothbauer, Mario; Conde, João P.; Ertl, Peter; Oliveira, Carla; Granja, Pedro L.
Abstract: Organ‐on‐a‐chip technology promises to revolutionize how pre‐clinical human trials are conducted. Engineering an in vitro environment that mimics the functionality and architecture of human physiology is essential toward building better platforms for drug development and personalized medicine. However, the complex nature of these devices requires specialized, time consuming, and expensive fabrication methodologies. Alternatives that reduce design‐to‐prototype time are needed, in order to fulfill the potential of these devices. Here, a streamlined approach is proposed for the fabrication of organ‐on‐a‐chip devices with incorporated microactuators, by using an adaptation of xurography. This method can generate multilayered, membrane‐integrated biochips in a matter of hours, using low‐cost benchtop equipment. These devices are capable of withstanding considerable pressure without delamination. Furthermore, this method is suitable for the integration of flexible membranes, required for organ‐on‐a‐chip applications, such as mechanical actuation or the establishment of biological barrier function. The devices are compatible with cell culture applications and present no cytotoxic effects or observable alterations on cellular homeostasis. This fabrication method can rapidly generate organ‐on‐a‐chip prototypes for a fraction of cost and time, in comparison to conventional soft lithography, constituting an interesting alternative to the current fabrication methods. Abstract : A microfabrication method based on xurography, capable of producing complex multilayered devices with integrated microactuators, suitable for organ‐on‐a‐chip applications, in a matter of hours is described. Microdevices fabricated with the technology are biocompatible and capable of mechanical actuation at physiological levels of strain. The method provides a fast alternative to current soft lithography methods, by reducing fabrication cost and time.